Theoretical Research on the Shear Mechanical Properties and Size Effect of Recycled Concrete Beams Without Stirrups - Chunyang Liu; Guangkai Zhou; Hao Wang; Yilin Wang (Buildings)
As a new type of building material with great potential, recycled concrete is playing a vital role in the context of the current construction industry’s pursuit of sustainable development. At present, the analysis method of recycled concrete structures is mainly based on the test results of small-scale specimens, but the reports relevant to the size effect of large components are not enough. Therefore, in this paper, the three-dimensional mesoscale numerical simulation is employed to conduct the static shear failure analysis of recycled concrete beams without web reinforcement. Based on existing experiments and verification of the rationality and accuracy of such numerical simulation, the influence of cross-sectional height, shear-span ratio, and the replacement rate of recycled aggregate on the shear mechanical properties and consequential size effect of recycled concrete beams are investigated. The research results reveal the dimension effect of nominal shear strength (NSS) and indicate that the shear strength of recycled concrete beams without stirrups shows a notable size-dependent effect, and the shear-bearing ability of recycled concrete beams reduces as the shear-span ratio and replacement rate of recycled aggregate rises. For every 20% increase in replacement rate, the shear-bearing capacity decreases by approximately 5%. The NSS shows a significant size effect, and it diminishes as beam height elevates. In addition, building on the material hierarchy of the Bažant size-effect law, a theoretical formula for the dimension effect on the shear strength of recycled concrete beams is proposed, considering the impact of shear-span ratio and replacement rate. The shear strength obtained from the supplied formula is subsequently compared with the standards of various countries, the results from existing calculation methods, and experiments. The accuracy and rationality of the supplied formula are verified. The research conclusion of this paper can provide a reference for engineering design.